KEEFEKTIFAN PETUGAS SURVEILANS KESEHATAN DEMAM BERDARAH DENGUE DALAM MENENTUKAN ANGKA BEBAS JENTIK - Resmi Lestariana Putri, Citra; Laksono, Budi (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Health surveillance officers of dengue hemorrhagic fever (DHF) was one of DHF prevention and control programs Semarang City. The aim of this research was to know the effectiveness of DHF surveillance officers to determine larvae-absence rate in Semarang City. This research was quantitative supported by qualitative study with descriptive survey design. Samples in this research were 57 DHF health surveillance officers determined by cluster sampling technique and 3 of them as informants to complete the quantitative data. Techniques of collecting data were interviews and documentation. Data analysis was done descriptively by determining the effectiveness formula and using Miles and Hubberman model for qualitative data. The study showed that DHF health surveillance officers in Semarang City has been effective. It showed from effectiveness result score of each component compared with the percentage table of program effectiveness that input aspect was effective (71%), process aspect was very effective (92%), and output aspect was effective (77%), even though there were still obstacles in each aspect.